A novel approach to evaluation of the cooling performance of pavement coatings. Issue 6 (14th December 2021) - Liang, S. H.; Niu, J. G.; Zeng, W. H.; Ying, Y. M.; Hui, W. C.
Abstract : On the basis of Grubbs' method and linear regression to exclude abnormal values, a novel experimental design and corresponding procedures as well as a theoretical strategy on data processing were investigated in an attempt to improve the evaluation accuracy of the cooling effects of road coatings. Five types of new cooling coatings were developed according to the requirements of current asphalt pavements and the optimal regression variables for cooling effects were selected. The results showed that the coefficients of regression formulas for the cooling effect of the different cooling coatings were around 0·99, suggesting that there was a significant correlation among the fitting variables. In particular, if the temperature of the asphalt pavement was 60°C, the cooling effect of the new coatings reached a value of nearly ten per cent, indicating that the developed data processing method could solve the inaccuracy problem of experimental data caused by different environmental factors.